The Legal Analysis of Signature Forgestion Handling Process in Land Selling by PPAT - Siti Mutmainah; Hepy Hapsari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The problems in this research, first: how Legal Analysis of the Process of Handling Signature Falsification in the Sale and Purchase of Land Conducted by PPAT in Semarang City (Live Study Case No. 505/Pdt.G/2020/Pn.Smg)? Second, what is the legal consequence of the Minuta Akta which is falsified by a notary? This research is a normative study. The results of the study conclude, first: the implications for the notary position can be categorized into four (4) aspects, namely, i) implications for deed engagement, ii) aspects of administrative positions; iii), Professional Aspects of Membership; vi), the criminal aspect. Second, the legal consequence of the Minuta deed which is falsified by the notary is that the deed only has the power of proof as an underhand deed, if the parties can prove the untruth of the authentic deed in court proceedings and result in the deed being canceled and the power of proof as the deed below hands will no longer apply.The problems in this research, first: how Legal Analysis of the Process of Handling Signature Falsification in the Sale and Purchase of Land Conducted by PPAT in Semarang City (Live Study Case No. 505/Pdt.G/2020/Pn.Smg)? Second, what is the legal consequence of the Minuta Akta which is falsified by a notary? This research is a normative study. The results of the study conclude, first: the implications for the notary position can be categorized into four (4) aspects, namely, i) implications for deed engagement, ii) aspects of administrative positions; iii), Professional Aspects of Membership; vi), the criminal aspect. Second, the legal consequence of the Minuta deed which is falsified by the notary is that the deed only has the power of proof as an underhand deed, if the parties can prove the untruth of the authentic deed in court proceedings and result in the deed being canceled and the power of proof as the deed below hands will no longer apply.